BUDGETING IN THE AI ERA: EXPLORING THE MODERATING EFFECTS OF AI UTILIZATION AND ISLAMIC FINANCIAL LITERACY ON SANTRI'S FINANCIAL LIFE) - Shofi Mustajibullah; Nurhidayah; Eny Zuhrotun Nasyi’ah (RADJA PUBLIKA, 2026)
One of the religious student groups in Indonesia with a fairly large scope is santri. Santri who are currently studying at university are known as Mahasantri, and are the object of this study. Their average financial resources range from Rp. 500,000 - Rp. 1,000,000, which is located in the lower middle class. Based on this, the financial problems experienced by Mahasantri are an illustration of this study to examine factors that can support financial life management , so that the daily needs of the students can be met. This study used a questionnaire on 375 students of the Nurul Jadid Probolinggo Islamic Boarding School . SmartPLS software version 03 was used to test the research hypothesis of the budgeting behavior variable as variable X, Islamic financial literacy as variable Z1, artificial intelligence utilization as variable Z2, and financial life management as variable Y. The test results of this study indicate that the first hypothesis of budgeting behavior has an effect on financial life management with a t-statistic of 4.089 and a p-value of 0.000. Meanwhile, the second and third hypotheses, namely the Islamic financial literacy variable with a t-statistic of 0.523 and a p-value of 0.601, and the artificial intelligence utilization variable with a t-statistic of 0.214 and a p-value of 0.830, were proven not to function as moderating variables. Therefore, the findings of this study are expected to provide a basis for policy-making by educational institutions related to supporting their students' personal finances. Institution managers can conduct regular financial literacy programs.